E-Governance and Decentralisation-Study of an Indian District - Kumar, T. (Journal of Rural Development, 2017)
The current era is witnessing the emergence of a new governance paradigm at the global, national and local levels. Information and Communication Technologies (ICTs) are fundamental to these systems of governance. Decentralised governance is a need in all countries. The same set of policy imperatives are behind the drive for decentralised governance as well as the drive for e-governance. So, there is a need for understanding of how e-governance can contribute to decentralisation of power. In this paper, a framework of e-governance for facilitating decentralisation has been evolved and tested in a district of Gujarat. Here, decentralisation is understood as a combination of its different kinds, viz., deconcentration, delegation, devolution and agencification. This is an empirical study done within the local self-governance units of a district in a rural context in India. This paper tries to measure the decentralisation of power within the governance machinery which can be facilitated by e-governance information systems. The relative empowerment of different branches of administration has been culled out. It was found that the empowerment of bureaucracy is the highest, followed by the empowerment of extra State actors. The elected representatives of the local self-governance machinery are not getting really empowered due to the e-governance process. This is a fundamental flaw in the design of these e-governance systems.